Glycolysis of poly(ethylene terephthalate) waste catalyzed by mixed Lewis acidic ionic liquids - Shuangjun, Chen; Weihe, Shi; Haidong, Cheng; Hao, Zhang; Zhenwei, Zhang; Chaonan, Fu (Journal of thermal analysis and calorimetry, 2021)
Widely used poly(ethylene terephthalate) (PET) material induces environmental concern on its wastes. In this paper, different 1-hexyl-3-methylimidazolium (Hmim) halometallates, including [Hmim]ZnCl 3 , [Hmim]CoCl 3 , [Hmim]FeCl 4 and [Hmim]CuCl 3 , are synthesized as Lewis acidic ionic liquids (LAIL) catalysts for PET degradation in excess ethylene glycol (EG). By using individual or mixed LAIL catalysts, product bis(hydroxyethyl) terephthalate (BHET) is characterized by FT-IR, 1 H-NMR and DSC et al. From the PET conversion and yield of BHET product, a synergistic effect is found in mixed [Hmim]ZnCl 3 and [Hmim]CoCl 3 complexes. 87.1% BHET from original PET wastes catalyzed by equimolar [Hmim]ZnCl 3 and [Hmim]CoCl 3 mixture is higher than any individual IL halometallate. The filter residues after removing the BHET products with different reacting time using [Hmim]ZnCl 3 and [Hmim]CoCl 3 as catalyst, respectively, are characterized by 1 H-NMR. The area ratio of the methylene protons of COO–CH 2 ( δ = 4.30 ppm) and the aromatic protons of the benzene ring ( δ = 8.12 ppm) of filter residues suggests that more by-products will be produced by [Hmim]ZnCl 3 because of its relatively higher catalytic activity in the chain scission stage. The glycolysis synergy comes from the balance between high reactivity of [Hmim]ZnCl 3 and high selectivity of [Hmim]CoCl 3 .